Pressure-induced physical properties in topological semi-metals MAs2M=Hf,Ti - Mithun Khan; Md. Rakib Hossain; Md. Lokman Ali (Results in Physics, 2023)
The present study employs first-principles DFT-based calculations within the generalized gradient approximation (GGA) to reveal various physical feature (including structural, elastic, mechanical, electronic, optical, as well as Debye temperature) of the topological semimetal MAs2 M=Hf,Ti under stress up to 50GPa. Mechanical and thermodynamic stability of the investigated materials are supported by Born stability criteria and formation energy. To learn more about the mechanical features of MAs2 M=Hf,Ti materials, we investigated at a variety of metrics such elastic constants, elastic moduli, Vickers hardness, machinability index, Kleinman parameter, and anisotropy factor. Interestingly, both Pugh’s ratio and Poisson’s ratio reveal that studied materials go through a brittle-to-ductile transition at different applied pressures. Due to the increase in elastic constants with increasing pressure, materials become more rigid and resistant to deformation, making them useful in various engineering fields. The studied materials are anisotropic, and their anisotropy factor changes significantly with rising pressure. The band structure analysis confirms that both materials are Weyl semi-metals, and the density of states reveals that the d orbital of Hf and Ti contributes significantly to DOS at EF. The electrical characteristics are strongly supported by the optical function. As external pressure increases, there is a corresponding increase in both the absorption coefficient and reflectivity. Their refractive index value falls and becomes flat at high energy, making them a high-density optical data storage media when exposed to the right light source. For both the material, pressure increases density, sound velocity, and Debye temperature, indicating that covalent bonds become stronger. The higher value of Debye temperature indicates the higher melting point of the studied compounds.